Perancangan Sistem Manajemen Gudang Non-Medis Menggunakan Metode Class-Based Storage Di RSUD UOBK - Zainida, Maya Revanola; Kusumawardani, Citra Dwi; Prabawati, Nurilia Fitri (Fakultas Teknik Universitas Tulang Bawang, 2025)
The Non-Medical Warehouse of UOBK Hospital was established in 2020 and has one door for entry and exit with non-medical goods arranged on shelves or directly under the floor, there are no recording sheets on each shelf, the arrangement of goods on the shelves still does not take into account the mobility of goods entering and exiting and there are no directions or markers. This research aims to provide suggestions in the form of warehouse management that needs to be completed, such as Standard Operating Procedures (SOP), Work Instructions and others as well as suggestions for reorganizing the warehouse layout by considering various aspects, characteristics of goods, warehouse area and so on starting from the circulation of goods in and out. slow, medium and fast. The results of this research are proposed SOPs, Job Descriptions, Work Instructions and a new warehouse layout for the Non-Medical Warehouse at UOBK Hospital in managing warehouse operations and warehouse layout by considering various aspects and characteristics of goods that are large or need to be placed in the back area. Goods with fast circulation with a percentage of 75% are placed with the entrance and exit in the left lane, namely sanitary goods and nutritional consumables on shelves N and O. There are differences in the initial warehouse layout which does not take into account the circulation of incoming and outgoing goods as well as the warehouse characteristics attached to Figure 6. Keywords: Layout, non-medical warehouse, warehouse management